Kinetics of water disinfection with Moringa Oleifera seeds extract - Bichi, Mustafa Hassan; Agunwamba, Jonah Chukwumemeka; Muyibi, Suleyman Aremu (International Institute for Science, Technology & Education (IISTE), 2012)
Moringa seeds extract was prepared using de-fatted seed cake and aqueous extraction. One mL of Moringa extract was added to 10mL of the cell cultures and incubated for 0, 30min, 60min, 90min, and 120min without agitation. Cell survival was assessed by making dilution series of bacterial suspensions obtained after each incubation period, plating on non-selective LB medium agar dishes, and incubating for 48hours at 37oC. Duplicates were made of every individual assay. Colonies were counted on dishes and the cell survival ratio was estimated by comparison to a control experiment where no Moring extract was added (0 min incubation time). Pseudo-first-order kinetics was fitted to the data. The log-inactivation of the “viable” organisms at time t (Nt) divided by the number of “viable” organisms at time zero (N0) was plotted as a function of chemical dose, Ct (mg min L -1). The coefficient of specific lethality, Ʌcw, was determined by linear regression using MINITAB for Windows Release 11.2 32Bit. A kinetic model was developed for the application of Moringa Oleifera seeds extract in water disinfection. The coefficient of specific lethality (Ʌcw) was determined as 3.76 L mg-1 min-1 for E.Coli inactivation using Moringa Oleifera seeds extracts. The mode of attack of the Moringa seeds extract on the E.Coli cell was explained as by rupturing the cell and damaging the intercellular components, when water dips in to the cell which causes it to swell more and burst leading to death.